Comparison of long-term efficacy and safety between cilostazol and clopidogrel in chronic ischemic stroke: a nationwide cohort study - Tsong-Hai Lee; Yu-Sheng Lin; Chia-Wei Liou; Jiann-Der Lee; Tsung-I Peng; Chi-Hung Liu (SAGE Publishing, 2020)
Background: Previous clinical trials showed a significant difference in efficacy and safety among antiplatelets in acute ischemic stroke (IS). The present study wished to compare the efficacy and safety head-to-head between cilostazol and clopidogrel in chronic IS. Methods: This open prospective cohort study recruited chronic IS patients with an index hospitalization between 2001 and 2013 from Taiwan National Health Insurance Research Database. In the 504,191 hospitalized patients, patients who had missing information and history of atrial fibrillation or rheumatic heart disease, received mechanical valve replacement or anticoagulants, expired during the index hospitalization, received follow-up ⩽6 months, or had recurrent stroke within 6 months after index stroke were excluded. Results: Among the 15,968 eligible patients, 502 patients who consistently received either cilostazol or clopidogrel from the 7th month after the index stroke were included for analysis after propensity score matching. The 3-year primary outcomes showed similar frequency of recurrent IS, all-cause mortality, and acute myocardial infarction (AMI), and similar frequency of intracerebral hemorrhage, gastrointestinal bleeding, and major bleeding between the cilostazol and clopidogrel groups. Subgroup analysis revealed that patients with a history of hypertension or gastrointestinal bleeding had a trend of having lower frequency of recurrent IS or major bleeding, respectively, in the cilostazol group. Conclusion: The present real-world study demonstrated no significant difference in efficacy and safety between cilostazol and clopidogrel in chronic IS. However, cilostazol might be better than clopidogrel in patients with a history of hypertension or gastrointestinal bleeding.